Analysis of The Impact of Using Audio-Visual Media on Student Learning Motivation - Rahayu, Ayu Puji; Saepulloh, Saepulloh; Ginanjar, Egi (JURNAL PENA EDUKASI, 2023)
Learning in the classroom must be carefully considered by the teacher, specifically how to create a conducive, enjoyable, active, interesting, and effective learning atmosphere aligned with the learning objectives. To achieve this goal, teachers are advised to utilize a variety of learning media, including audio-visual tools, to enhance student learning motivation. This study aims to analyze the impact of using audio-visual media on learning motivation, quantify the extent of the effect, and establish a linear regression equation. The linear regression equation is employed to determine the nature of the relationship between the use of audio-visual media and learning motivation, whether it is positive or vice versa. This research employs a quantitative approach through a survey method. The data collection technique involves using a questionnaire. Derived from the outcomes of this investigation, it is evident that there is a notable effect of audio-visual media usage on student learning motivation. This is substantiated by obtaining a significant value of 0.001 (<0.05) and further supported by the analysis of the t-score, which is 3.986 (>2.003). Consequently, there is a significant influence of audio-visual media usage on students' learning motivation.